Reintroducing extirpated herbivores could partially reverse the late Quaternary decline of large and grazing species. Issue 4 (15th February 2021) - Schowanek, Simon D.; Davis, Matt; Lundgren, Erick J.; Middleton, Owen; Rowan, John; Pedersen, Rasmus Ø.; Ramp, Daniel; Sandom, Christopher J.; Svenning, Jens‐Christian
Abstract: Aim: Reinstating large, native herbivores is an essential component of ecological restoration efforts, as these taxa can be important drivers of ecological processes. However, many herbivore species have gone globally or regionally extinct during the last 50, 000 years, leaving simplified herbivore assemblages and trophically downgraded ecosystems. Here, we discuss to what extent trophic rewilding can undo these changes by reinstating native herbivores. Location: Global. Time period: We report functional trait changes from the Late Pleistocene to the present, and estimated trait changes under future scenarios. Major taxa studied: Wild, large (≥ 10 kg), terrestrial, mammalian herbivores. Methods: We use a functional trait dataset containing all late Quaternary large herbivores ≥ 10 kg to look at changes in the body mass and diet composition of herbivore assemblages, a proxy for species' ecological effects. First, we assess how these traits have changed from the Late Pleistocene to the present. Next, we quantify how the current body mass and diet composition would change if all extant, wild herbivores were restored to their native ranges (and if no functional replacements were used), exploring scenarios with different baselines. Results: Defaunation has primarily removed large and grazing herbivores. Reinstating extant herbivores across their native ranges would reverse these changes, especially when reinstating them to their prehistoric distributions. It would partially restore herbivore body mass and diet composition to pre‐anthropogenic conditions. However, in the absence of complementary interventions (e.g., introducing functional replacements), many herbivore assemblages would remain down‐sized and browser dominated, relative to pre‐anthropogenic conditions. Main conclusions: Many terrestrial herbivore assemblages—and hence ecosystems—would remain trophically downgraded, even after bringing back all extant, native herbivores. Therefore, complementary interventions would be required to achieve complete functional restoration. Nevertheless, our findings suggest that reintroducing the remaining native herbivores would diversify the herbivory and disturbances of herbivore assemblages.